(untitled) (Research, Society and Development, 2022)
For a smile to be considered harmonious, several factors should be analyzed and taken into consideration, such as the proportion of the dental structure, which should be in balance with the labial musculature and gingival exposure. In situations where the individual has a gingival exposure above 3-4 mm when smiling, the presence of a disharmonic smile, called gummy smile, is observed. The aim of this study is to report a clinical case of gummy smile correction using a flapless surgery. A 24-year-old female patient sought dental care with an aesthetic dissatisfaction with her smile. A clinical evaluation and periodontal clinical examination of all teeth were performed. The patient was diagnosed with altered passive eruption, and the proposed treatment was a flapless gingivoplasty, which is a minimally invasive treatment with fast healing. The surgical procedure was uneventful, the post-operative period was uneventful, the patient had no complaints, no signs of inflammation and good healing, and the periodontium had a good healing condition. A good diagnosis and the choice of the correct technique for the treatment of gummy smile is essential to meet the expectation from the aesthetic and functional point of view, and to obtain treatment success.